2020
DOI: 10.2147/nss.s253281
|View full text |Cite
|
Sign up to set email alerts
|

<p>Obstructive Sleep Apnea Syndrome: A Preliminary Navigated Transcranial Magnetic Stimulation Study</p>

Abstract: Purpose: An increase in resting motor threshold (RMT), prolonged cortical silent period duration (CSP), and reduced short-latency afferent inhibition (SAI), confirmed with previous transcranial magnetic stimulation (TMS), suggest decreased cortical excitability in obstructive sleep apnea syndrome (OSAS). The present study included MRI of OSAS patients for navigated TMS assessment of the RMT, as an index of the threshold for corticospinal activation at rest, and SAI as an index of cholinergic neurotransmission.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(159 reference statements)
1
1
0
Order By: Relevance
“…SAI was significantly reduced in apneic patients compared to healthy controls, and SAI level was strongly correlated with neuropsychological scores, suggesting that cognitive deficits in OSAS may be, at least in part, related to impaired cholinergic neurotransmission, presumably caused by the intermitted nocturnal hypoxemia ( Nardone et al, 2016a ). A more recent navigated TMS study demonstrated an increased rMT and reduced SAI in OSAS, thus confirming previous findings of impaired cortical afferent inhibition in these patients ( Rogić Vidaković et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…SAI was significantly reduced in apneic patients compared to healthy controls, and SAI level was strongly correlated with neuropsychological scores, suggesting that cognitive deficits in OSAS may be, at least in part, related to impaired cholinergic neurotransmission, presumably caused by the intermitted nocturnal hypoxemia ( Nardone et al, 2016a ). A more recent navigated TMS study demonstrated an increased rMT and reduced SAI in OSAS, thus confirming previous findings of impaired cortical afferent inhibition in these patients ( Rogić Vidaković et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…Experimental research and neuroimaging studies show effects of intermittent hypoxia on sleepiness, memory and executive dysfunction. In individuals with OSAS, such changes have been attributed to reduced cell neurogenesis and density of the hippocampus [17,50,29], the frontal cortex and generalized grey matter [35,2,39,11].The abnormal changes of gray matter (GM) and white matter may be the important pathological basis of OSAS leading to neurocognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%